ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI MINAT MAHASISWA DALAM MENEMPUH PENDIDIKAN DI SEKOLAH TINGGI AGAMA ISLAM TEBINGTINGGI DELI - Indah Dina Pratiwi (Universitas Islam Negeri Sumatera Utara Medan, 2017)
This study aims to analyze more about the forms of extrinsic interest (interest related to the end goal of an activity) students and school environment factors that affect student interest in education at Islamic High School Tebingtinggi Deli Tebingtinggi City in 2016- 1017. This research is a qualitative research with phenomenological approach. Technique of collecting data by interview, observation, and documentation. The subjects of this study are students of Islamic religious education study program of Islamic High School Tebingtinggi Deli Tebingtinggi City in 2016-1017. The collected data is analyzed by using qualitative descriptive analysis technique that is collected data as it is compiled, interpreted and then analyzed, for further drawn conclusion. This study found that the forms of students' extrinsic interest in education at Islamic High School Tebingtinggi Deli Tebingtinggi City in 2016-1017 are: to become a teacher, to deepen and / or add knowledge, to obtain a degree, to become a teacher with status Civil servants, to be successful and noble, and to improve the mindset. Furthermore, the school environment factors that influence the students' interest in studying at Islamic High School of Tebingtinggi Deli are: first, lecturing time factor and lecturer relation factor with the student as the most dominant factor influencing student interest, secondly, student relation factor with student And curriculum factors of majors as factors influencing student interest, thirdly, lecturer teaching method factor and facility factor of High School as a factor influencing student interest, and fourth, lecture discipline factor as a factor that less influence student interest.